Hubungan Pengetahuan dan Sikap Remaja Putri Tentang Keputihan dan Praktek Personal Hygiene di Hunian Sementara Pasca Bencana Alam: Relationship Between Knowledge with Attitudes of Young Women about Leucorrhoea and Personal Hygiene Practices in Temporary Shelters Post-Natural Disaster - Enggar, Enggar; Riska Ratna Sari (Poltekkes Kemenkes Palu, 2020)
Post-disaster causes survivors to occupy temporary shelters provided with cramped conditions and all-emergency. Survivors who need attention to reproductive health are young women. The study aimed to determine the relationship of knowledge with attitudes of young women about vaginal discharge and the practice of personal hygiene in Temporary Shelter Petobo and Gawalise. This study used analytic research Cross-Sectional Study. The number of samples was 47 young women—analysis by Rank Spearman test. The results of this study obtained the Relationship between Knowledge (p-value=0,231; r=0,178) with attitudes of young women about leucorrhoea and practices personal hygiene. It is expected that an increase in personal education hygiene in young women living in temporary shelters, due to the cramped conditions in the humid and less of lavatory can cause disease